1986
DOI: 10.1146/annurev.ns.36.120186.002223
|View full text |Cite
|
Sign up to set email alerts
|

Recent Nuclear Structure Studies in Rapidly Rotating Nuclei

Abstract: The fo rmation of evaporation residues at large angular momentum in fusion-evaporation reactions is discussed many places in the literature (e.g. I).3Yrast is a neologism (8) from the superlative fo rm of the Nordic word yr meaning "dizzy." The yrast state is the most "dizzy." or that with the largest angular momentum, fo r a given excitation energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 67 publications
3
34
0
Order By: Relevance
“…4). This behaviour has been generally observed in well deformed nuclei [16], and has suggested that the transitions in the moving bump originate from SD states, since such a bump should not be expected from ND spherical states, and one does not observe it in coincidence with transitions in the more collective triaxial well of 143 Eu [17]. Angular anisotropies, moment of inertia determination and lifetimes analysis have confirmed that the bump originates from highly collective rotationally damped E2 transitions generated by SD states [12].…”
Section: The Super-deformed Quasi-continuum In 14eusupporting
confidence: 67%
“…4). This behaviour has been generally observed in well deformed nuclei [16], and has suggested that the transitions in the moving bump originate from SD states, since such a bump should not be expected from ND spherical states, and one does not observe it in coincidence with transitions in the more collective triaxial well of 143 Eu [17]. Angular anisotropies, moment of inertia determination and lifetimes analysis have confirmed that the bump originates from highly collective rotationally damped E2 transitions generated by SD states [12].…”
Section: The Super-deformed Quasi-continuum In 14eusupporting
confidence: 67%
“…The functions G(r, r ′ , ε) and F + (r, r ′ , ε) are the Fourier transforms of the Green's functions 4) where Φ N and Φ N +2 are the eigenfunctions of the ground state of a system of N and N + 2 interacting particles, ψ + and ψ are creation and annihilation operators in the Heisenberg representation, T is the time ordering operator, and ε F is the Fermi energy (the chemical potential of the system). The contour C consists of the real axis and an infinite semicircle in the upper half-plane.…”
Section: Cranked Gor'kov Equationsmentioning
confidence: 99%
“…[3] the disappearance of static pairing leads to a change of the excitation spectrum, from the quasiparticle to the particle-hole spectrum. Unfortunately, the application of this criterion to normal deformed (ND) bands [3,4,5] shows that this method is not free from ambiguities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are very complicated and lose simplicity of the model. On the other hand, by taking into account the effect of rotation unperturbatively, the mean-field theory has been extended in the rotating frame: The cranking model or the Cranked Shell Model (CSM) [5], which is simple and yet microscopic, has been successfully applied to understand various high-spin phenomena [6] such as backbending of moment of inertia. Recently, this cranking model has been further extended in such a way to include the tilting degrees of freedom of rotation-axis relative to the deformed shape; the Tilted Axis Cranking (TAC) model [7,8,9] (the conventional cranking is called the Principal Axis Cranking (PAC) model, instead), which gives nice interpretations of new types of nuclear rotational motions, e.g.…”
Section: Introductionmentioning
confidence: 99%